Effect of processing methods on the cytotoxicity of methyl methacrylate-based ocular prostheses: An in vitro study - da Silva, Emily Vivianne Freitas [UNESP]; Goiato, Marcelo Coelho [UNESP]; Bitencourt, Sandro Basso [UNESP]; Finer, Yoav; Brito, Victor Gustavo Balera; Takamiya, Aline Satie [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; dos Santos, Daniela Micheline [UNESP] (Elsevier, 2021)
The study evaluated the influence of cycles and methods of an ocular prosthesis resin on cytotoxicity toward human conjunctival cells. Resins were polymerized by water bath (WB, 74 °C or 100 °C for 30 min to 9 h), microwave (MW, 1200 W, 3 to 14 min and 30 s at 0 to 720 W), or autopolymerization (AP, room temperature for 20 min ± 60 °C for 30 min). Degree of conversion (DC), cytotoxicity, level of inflammatory mediators, gene expression of different markers, and apoptosis were evaluated. Data were submitted to ANOVA and Tukey test (p < 0.05). WB with longer processing time at higher temperature had highest DC (85.6%) and higher TGF β1-gene expression (1.39); long cycle low power MW showed lowest DC (69.6%), lower cell proliferation (85.4%, MTT), and large IL-2 release (39,297 ng/mL). AP with additional processing time showed lower cell proliferation (75.3%, Alamar Blue), and AP polymerized at room temperature showed higher CASP 9-gene expression (1.21). AP methods showed higher IL-6 release (>277 pg/mL). Short cycle medium power MW had higher IL-23 release (534.2 pg/mL). MW (long and short cycles) and AP polymerizations have triggered a more intense inflammatory response. Among methods recommended by the manufacturer, WB showed high DC and less cytotoxicity.
Keywords: Cellular immune response; Cytotoxicity; Methyl methacrylate; Ocular prosthesis